2013
DOI: 10.1371/journal.pone.0060955
|View full text |Cite
|
Sign up to set email alerts
|

Combined Approaches for Drug Design Points the Way to Novel Proline Racemase Inhibitor Candidates to Fight Chagas’ Disease

Abstract: Chagas’ disease is caused by Trypanosoma cruzi, a protozoan transmitted to humans by blood-feeding insects, blood transfusion or congenitally. Previous research led us to discover a parasite proline racemase (TcPRAC) and to establish its validity as a target for the design of new chemotherapies against the disease, including its chronic form. A known inhibitor of proline racemases, 2-pyrrolecarboxylic acid (PYC), is water-insoluble. We synthesized soluble pyrazole derivatives, but they proved weak or inactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 41 publications
0
31
0
Order By: Relevance
“…Taking into account that Tc PRAC-A and TcPRAC-B participate in T. cruzi development in vertebrates and vectors and have been incriminated as host defence factors [ 9 - 12 , 19 , 22 , 55 ], it is tempting to speculate whether DTU-specific Tc PRAC enzymes can contribute to differential degrees of metacyclogenesis, parasitemias and virulence. T. cruzi of different DTUs interacts differently with the host, induces distinct immune responses and infections ranging from highly lethal to virtually asymptomatic, contributing to variable clinical forms of Chagas disease.…”
Section: Resultsmentioning
confidence: 99%
“…Taking into account that Tc PRAC-A and TcPRAC-B participate in T. cruzi development in vertebrates and vectors and have been incriminated as host defence factors [ 9 - 12 , 19 , 22 , 55 ], it is tempting to speculate whether DTU-specific Tc PRAC enzymes can contribute to differential degrees of metacyclogenesis, parasitemias and virulence. T. cruzi of different DTUs interacts differently with the host, induces distinct immune responses and infections ranging from highly lethal to virtually asymptomatic, contributing to variable clinical forms of Chagas disease.…”
Section: Resultsmentioning
confidence: 99%
“…The structure also revealed that the cyclopentane moiety of the inhibitor could adopt multiple conformations, suggesting that space was available for further chemical modulations. Interestingly, the conformation of the active site in the co-crystal structures with our inhibitors was highly similar to that of the transitional intermediate models built to identify the first inhibitors by virtual screening [ 17 ]. This could be viewed as a demonstration of the relevance of molecular modeling in enlarging chemical space search in drug design.…”
Section: Introductionmentioning
confidence: 87%
“…Inactivation kinetics were performed at different inhibitor concentrations as described previously [ 17 , 26 , 27 ]. A program developed in-house was used to fit the data [ 17 , 26 , 27 ]. As global fitting appeared difficult and was unsuccessful, single exponential models were simply fit to the individual kinetics.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TcPRAC is a promising target for the development of a new therapy against Chagas disease since parasites are no longer viable when PRAC genes are knocked down or more virulent if PRAC genes are over expressed [ 220 ]. Two compounds, which are irreversible competitive inhibitors of TcPRAC, were able to inhibit the mammalian host cell infection [ 221 ].…”
Section: Therapeutic Targetsmentioning
confidence: 99%